Ras Bitwädded Mäkonnen Endalkachäw: Some Thoughts on His Life and Work - Fellman, Jack (Research in African literatures, 1996)
Ras Bitwadded Makonnen Endalkachaw (1892-1963) was a leading Ethiopian statesman and writer of fiction, plays, poems and essays. Many of his works have been translated from the original Amharic to English. He was an advocate for protection of traditional Ethiopean religious practices and fuedal society from modern influences.